(untitled) (Global Journal of Management and Business Research, 2018)
The ERP (Enterpise Resource Planning) system is designed to coordinate the resources, information and activities required in the company’s business processes. Successful implementation of ERP system can provide an increase in terms of effectiveness and efficiency of business operations at the company. But the realization implementation of ERP systems into a very complex process, so that not infrequently encountered failure in its application. Failure in the implementation of ERP systems resulted in enormous losses for the company. Thus the correct analysis is needed in order to achieve the successful implementation of ERP to benefit from its application. This research is a quantitative research using three independent variables: top management support, effective project management, and user engagement. The purpose of this research is to analyze the critical factors that can improve the success of the implementation process of ERP systems in SMEs in East Kalimantan. The method used is multiple linear regression analysis. The results of the research simultaneously show that there is a significant influence between the key factors on the success of implementation. While the partial factor of top management support, effective project management quite significant effect. However, the factor of user engagement has no significant effect on the success of ERP implementation.